PENATALAKSANAAN HOLISTIK PASIEN PEREMPUAN USIA 55 TAHUN DENGAN PENYAKIT PARU OBSTRUKTIF KRONIS (PPOK) DAN RIWAYAT TUBERCULOSIS (TB) PARU MELALUI PENDEKATAN DOKTER KELUARGA DI WILAYAH PUSKESMAS PASAR AMBON - Noviyanti, Dwi Wulan; Saftarina, Fitria (CV. Jasa Sukses Abadi, 2024)
Chronic obstructive pulmonary disease (COPD) is defined as a lung disease with clinical symptoms as shortness of breath, coughing, phlegm production due to airway abnormalities that cause persistent airflow obstruction. This airflow obstruction in COPD is progressive and often associated with chronic-inflammation caused by exposure to noxious substances, such as cigarette smoke. Tuberculosis (TB) is a contagious-infectious disease caused by Mycobacterium-tuberculosis and most often manifests in the lungs (pulmonary TB), although-M.Tb can also infect other organs (extrapulmonary TB). History of pulmonary TB could cause permanent-damage to lung-anatomy and associated with loss of lung-function, such as bronchiectasis, fibrosis, or post-TB emphysema, which can increase the risk of COPD. Research by Fan H et al in 2021 stated that there was a risk of COPD in patients with a previous history of pulmonary TB. Providing family doctor services rooted in evidence-based medicine involves the identification of risk factors and clinical issues, along with the management of patients, all within a patient centered and family oriented problem solving framework. This study involves a case-report-analysis. Primary data were gathered through history taking, physical examinations, and home visits. The evaluation is conducted based on a comprehensive diagnosis-spanning the initial, process-oriented, and final phases of the study, using both quantitative and qualitative methods. Interventions for the patient-consisted of educational measures for patients and their families using posters and direct discussions. Following these interventions, there was an observed improvement in both knowledge and behavioral-changes both patient and family-behaviors, as evidenced by improvements in the final holistic-diagnostics.